Respon Fisiologis Domba Lokal Dengan Frekuensi Pemberian Pakan dan Taraf Konsentrat Limbah Ulat Hongkong (Tenebrio molitor) yang Berbeda - M. A. H. Kirjin; S. Rahayu; M. Baihaqi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The aim of this research was to evaluate the effect of feeding frequency and level of Tenebrio molitor’s waste concentrate (TMC) on the physiological response of local sheep. A total 18 rams aged Io (8 months) with an average body weight of 14.72±2.44 kg (CV 16.91%) were used in this research. The reserch using 3x2 factorial randomized block design. Firts treatment was feeding frequency (2, 3 and 4 times/day) and second treatment was level of TMC ration (70% and 35% of TMC). The variables observed were physiological responses (pulse rate, rectal temperature, and respiration rate). The data were analyzed by ANOVA. The results showed that there was interaction effect between feeding frequency and TMC level on pulse rate and rectal temperature of sheep. The level of 35% TMC was significantly higher (P<0.05) on respiration rate than 70% TMC when the sheep feed in the morning. The research concluded that frequency of feeding and the level TMC had a significant effect on physiological responses in local rams.